2022
DOI: 10.3390/molecules27123858
|View full text |Cite
|
Sign up to set email alerts
|

Stress Buffering and Longevity Effects of Amber Extract on Caenorhabditis elegans (C. elegans)

Abstract: Amber is a fossilized tree resin historically used in wound healing and stress relief. Unfortunately, there is no concrete scientific evidence supporting such efficacy. Here, the stress buffering and longevity effect of Amber extract (AE) in Caenorhabditis elegans (C. elegans) was investigated. Survival assays, health span assays, Enzyme-Linked Immunosorbent Assay (ELISA), Stress biomarker detection assays, Green Fluorescence Proteins (GFP), Real Time quantitative PCR (RT-qPCR) and C. elegans mutants were empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 60 publications
1
4
0
Order By: Relevance
“…When mice were subjected to psychological stress through TST, an increased accumulation of the lipid-peroxidation product MDA was observed because of oxidative damage, which was significantly reduced by amber supplementation. These findings confirmed the antioxidant effect of amber observed in our previous study on Caenorhabditis elegans, in which amber treatment significantly protected worms from H 2 O 2induced oxidative stress and increased the expression of the antioxidant genes sod-3, gst-4, and ctl-1 [11].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…When mice were subjected to psychological stress through TST, an increased accumulation of the lipid-peroxidation product MDA was observed because of oxidative damage, which was significantly reduced by amber supplementation. These findings confirmed the antioxidant effect of amber observed in our previous study on Caenorhabditis elegans, in which amber treatment significantly protected worms from H 2 O 2induced oxidative stress and increased the expression of the antioxidant genes sod-3, gst-4, and ctl-1 [11].…”
Section: Discussionsupporting
confidence: 91%
“…However, there are no reports on its antidepressant effect. We previously demonstrated that amber might exhibit an anti-stress effect through the regulation of HPA hyperactivity [11]. Thus, we hypothesized that amber possesses an antidepressant effect via the regulation of hormones in the HPA axis and factors contributing to oxidative stress.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is widely used as one of the first-choice model organisms to study aging, stress resistance, mitochondrial biology, and apoptosis at the molecular level [13,14], mainly due to the short life span for approximately 15-21 days, as well as its completely sequencing and annotation of all the genes [15], the abundance of mutant strains [16]. The most important fact that results of trials on C. elegans can be predictive of outcomes in higher organisms [17]. There is little difference of mitochondrial biologybetween C. elegans and humans [14].…”
Section: Introductionmentioning
confidence: 99%
“…This is primarily attributed to its short lifespan of approximately 15–21 days, its comprehensive sequencing and annotation of all genes [ 15 ], and the availability of numerous mutant strains [ 16 ]. Importantly, findings from studies conducted on C. elegans have been shown to have predictive value for outcomes in higher organisms [ 17 ]. Furthermore, there is minimal disparity in mitochondrial biology between C. elegans and humans [ 14 ].…”
Section: Introductionmentioning
confidence: 99%